HARDINESS LEVEL AND MUSIC LISTENING ASSOCIATED WITH BURNOUT AMONG UNDERGRADUATE STUDENTS IN A PUBLIC UNIVERSITY IN MALAYSIA - Nursyafini Awaluddin; Azleen Aziz; Azmir Ahmad; Wan Hasliza Wan Mamat; Nurasikin Mohamad Shariff (Journal of Islamic, Social, Economics and Development, 2024)
Burnout among the university students has negative impact on daily educational tasks and poor results could ensue, whereas students may cope with it via music which is preferred by the young population. The aim of this study is to examine the association between music listening and burnout among the university students in Malaysia. Methods: A cross-sectional study with convenient sampling was conducted among 381 undergraduate students in one public university in Malaysia. A set of questionnaires comprised of sociodemographic data, Maslach Burnout Inventory Student Survey (MBI-SS) and Hardy Personality Profile was distributed via online survey. MANOVA test were performed to examine the relationship between the burnout, music listening characteristics and sociodemographic characteristics. Results: Music listening among the undergraduate students in increased frequency of listening, duration of listening (more than average), good CGPA, and moderate hardiness level are associated with students’ high academic efficacy. The students’ perceived calming effect of music listening and listening in less than average was associated with lower burnout level. Conclusion: The benefits of music listening perceived as calming among undergraduate students were evident for lessening burnout. Increase in its duration and frequency and could improve academic efficacy of the undergraduate students. The current finding warrants more attention from the universities to promote the culture of cultivating music within the academic vibes for supporting academic efficacy. More research is needed to examine the effect of music in different genres on other populations of interest and in other contexts of mental health issues.